مكافحة جريمة غسل الأموال في القانون السوداني مقارنا بالقانون البريطاني والماليزي - كردمان، أفضال السيد صديق (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2017)
Money laundering has become one of the most important and complicated financial crimes. This is due to its vast outreach and the difficulty of identifying, controlling and finding an effective solution to eliminate it. This research aims to study the crime of money laundering from the Sudanese, British and Malaysian legal perspectives. The paper discusses and analyses the legislations of these three countries and Islamic law perspective, in order to determine the suitable method to tackle money laundering in these countries. The issue of combating the crime of money laundering is one of the fundamental topics to be studied and appreciated. The crime of money laundering has evolved and increased in complexity and new methods are needed to combat it. The researcher incorporated a number of scientific research methodologies; the descriptive analytical method and the comparative method as well as library research. The study found that Britain and Malaysia have shown vigorous efforts fighting the crime of money laundering as reflected in the legislations, whereas Sudan's efforts towards it are still under way. Effective legislative mechanisms and the establishment of competent regulatory agencies to combat this crime are essential in Sudan. However, a blanket adoption is not suitable and modifications are necessary to suit the situation in Sudan. The research also concluded that the principles laid down in Islamic Jurisprudence may contribute to the prevention of money laundering and may strengthen anti-money laundering legislation. Finally, the researcher has put forward several recommendations and proposals to contribute in the development of better control mechanisms for this dangerous crime.